Epigenetic regulation of banana fruit ripening: global and specific DNA methylation profile, and characterization of DNA methylation-related genes - Dina Hermawaty; Mita Azzahra Putri; Sekar Prabhandiya; Fenny Martha Dwivany; Karlia Meitha (Cogent Food & Agriculture)
Climacteric fruits like bananas often experience significant post-harvest losses due to rapid ripening. This study investigated the molecular processes behind banana ripening, focusing on DNA methylation and its role in regulating gene expression through epigenetics. Physiological changes during ripening included alterations in peel color, fruit firmness, and total soluble solids, with marked increases in starch degradation, brown spot formation, and ethylene production by day 7. Global DNA methylation patterns, analyzed using methylation-sensitive amplification polymorphism, revealed an increase in methylation levels on day 3 of ripening. Key genes involved in DNA methylation and demethylation were identified through in silico gene and protein analysis of Musa acuminata. These include three methyltransferases (MaDRM2-A, MaDRM2-B, and MaDRM2-C) and three demethylation-related genes (MaDML-A, MaDML-B, and MaROS1). Expression levels of MaDRM2-A, MaDRM2-B, MaDML-A, and MaROS1 significantly increased by day 3, suggesting their involvement in early ripening processes. Additionally, methylation dynamics were observed on CpG islands of two critical transcription factors, MaMADS1 and MaMADS2, though gene regulation was unaffected. The study highlights that DNA methylation regulation precedes visible physiological changes in ripening, offering insights into the molecular mechanisms governing fruit ripening and potential strategies to enhance quality and extend shelf life.